2011
DOI: 10.2478/s11535-011-0103-z
|View full text |Cite
|
Sign up to set email alerts
|

In vitro plantlet production of the endangered Pinguicula vulgaris

Abstract: This study describes the development of a micropropagation protocol for Pinguicula vulgaris using cultures initiated from in vitro produced seedlings. P. vulgaris is a carnivorous plant with a northern, disjunctly circumpolar distribution and specific habitat requirements, and is hence becoming increasingly rare. Shoot proliferation was significantly influenced by Murashige and Skoog (MS) macronutrient concentration, showing higher proliferation rates in 1/4MS, but was not affected by the addition of 0.1 mg/L … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
0
4
0
1
Order By: Relevance
“…Because inbreeding depression tends to be ameliorated in ex situ conditions compared to natural habitats (Hauser & Loeschcke, 1994;Keller & Waller, 2002), we measured seed germination and seedling survival in both ex situ and in situ conditions. Ex situ germination was evaluated following protocols developed for Pinguicula (Gonçalves, Escapa, Grevenstuk, & Romano, 2008;Grevenstuk & Romano, 2012). We deposited 36 seeds per fruit on Petri dishes containing 25 mL of bacteriological agar (Sigma-Aldrich A5306, Merck KGaA, U.S. available www.sigmaaldrich.com/).…”
Section: Fitness Componentsmentioning
confidence: 99%
“…Because inbreeding depression tends to be ameliorated in ex situ conditions compared to natural habitats (Hauser & Loeschcke, 1994;Keller & Waller, 2002), we measured seed germination and seedling survival in both ex situ and in situ conditions. Ex situ germination was evaluated following protocols developed for Pinguicula (Gonçalves, Escapa, Grevenstuk, & Romano, 2008;Grevenstuk & Romano, 2012). We deposited 36 seeds per fruit on Petri dishes containing 25 mL of bacteriological agar (Sigma-Aldrich A5306, Merck KGaA, U.S. available www.sigmaaldrich.com/).…”
Section: Fitness Componentsmentioning
confidence: 99%
“…Revista Bio Ciencias 4(3): 179-188 Enero 2017 e independizarlos, también observamos formación espontánea de raíces en más del 70 % de brotes después de 30 días de incubación, lo que puede deberse a la presencia de altos niveles de auxinas endógenas como se ha encontrado para otras especies (Malá et al, 2005). Similarly to what Grevenstuk and Romano (2012), and Clapa et al, (2010) found in P. vulgaris, reporting a spontaneous rooting in a medium with no regulators. This medium allowed not only the devitrification and freed of shoots, but we also observed the spontaneous formation of roots in more than 70 % of shoots after 30 days of incubation, which can be due to the presence of high levels of endogen auxins as it has been found in other species (Malá et al, 2005).…”
Section: Discussionunclassified
“…Collection of seeds and development of additional plant propagation protocols will assist in the conservation and preservation of these rare plants. Already, propagation protocols are available for several Pinguicula species that could be used or modified for Southeast US Pinguicula species (Gonçalves et al 2008;Saetiew et al 2011;Grevenstuk and Romano 2012;Di Martino et al 2014). Any ex-situ collections for Pinguicula species should be in conjunction with botanical gardens in Florida such as Bok Tower Gardens and Fairchild Tropical Botanic Garden and the International Carnivorous Plant Society.…”
Section: Researchmentioning
confidence: 99%